Analysis of option trading strategies based on the relation of implied and realized S&P500 volatilities - Alexander Brunhuemer; Gerhard Larcher; Lukas Larcher (ACRN Journal of Finance and Risk Perspectives (JOFRP), 2021)
In this paper, we examine the performance of certain short option trading strategies on the S&P500 with backtesting based on historical option price data. Some of these strategies show significant outperformance in relation to the S&P500 index. We seek to explain this outperformance by modeling the negative correlation between the S&P500 and its implied volatility (given by the VIX) and through Monte Carlo simulation. We also provide free testing software and give an introduction to its use for readers interested in running further backtests on their own.
Keywords: 330; Option-trading; S&P500-index; Implied volatility; Realized volatility